Modern Printed-Circuit Antennas - Al-Rizzo, Hussain (IntechOpen, 2020)
This book presents in-depth information on a variety of the latest developments in modern printed-circuit antennas written by several prominent authors in the field. This book consists of nine chapters covering a wide range of recent research topics. The topics covered include low-profile metamaterial-based adaptive beamforming techniques, high performance meta-surface antennas, fractal antennas, reconfigurable antennas for 5G systems operating at 60 GHz, radiation pattern synthesis of planar arrays using parasitic patches fed by a small number of active elements, decoupled and de-scattered monopole MIMO antenna arrays with orthogonal radiation patterns, ultra-wide band antennas with defected ground plane and microstrip line fed for Wi-Fi/Wi-Max/DCS/5G/satellite communications, and design, fabrication, and characterization of wearable textile antennas with high body-antenna isolation.